Favela, criminalité violente et politique à Rio de Janeiro - Luiz Antonio Machado da Silva (Confins)
The text is designed as an empirical treatment of sociopolitical integration process characteristic of the city of Rio de Janeiro. A scheme for the "flattening" of disputes on social control is briefly proposed, starting from militarized developmentalism implanted by the dictatorship, based on the doctrine of "national security", and the widespread concern about threats facing the continuity of daily routines contained the collective representations of "urban violence" whose soul is associated with the arrival on the scene of crime related to illicit drug trafficking, competition for economic space between its different armed gangs and clashes with the police(s). The central argument is that with the hyper-politicization of the change that took place in the early 1980s, during the campaign for the State government of Leonel Brizola, a very controversial figure, a new form of social conflict is based on what has been called a "metaphor of war" and has replaced the secular agenda of the debate around the "problem of the slum" - their place in the city - now the topic as an issue related to control the repressive policy of urban peripheries. The superposition of the "everyday security problem" to "slum problem" reproduces the traditional processes of spatial segregation, but now with a widespread "fear of the next" and the presence in the favelas gang drugs, which significantly reduces the chances of maintaining local collective action and the popularization of their requests.